2004
DOI: 10.1210/rp.59.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroid Hormone on the Cardiovascular System

Abstract: Increased or reduced action of thyroid hormone on certain molecular pathways in the heart and vasculature causes relevant cardiovascular derangements. It is well established that overt hyperthyroidism induces a hyperdynamic cardiovascular state (high cardiac output with low systemic vascular resistance), which is associated with a faster heart rate, enhanced left ventricular (LV) systolic and diastolic function, and increased prevalence of supraventricular tachyarrhythmias -namely, atrial fibrillation -whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
339
2
23

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(373 citation statements)
references
References 110 publications
9
339
2
23
Order By: Relevance
“…However, Olkowski et al (1999) and Olkowski and Classen (1998) have published results indicating that RVH and right ventricular failure are secondary to left ventricular failure. This may be brought into relation with changed thyroid function and the lower thyroid hormone levels in postnatal birds when incubated at high altitude because subclinical hypothyroidism causes left ventricle dysfunction, at least in mammals (Fazio et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, Olkowski et al (1999) and Olkowski and Classen (1998) have published results indicating that RVH and right ventricular failure are secondary to left ventricular failure. This may be brought into relation with changed thyroid function and the lower thyroid hormone levels in postnatal birds when incubated at high altitude because subclinical hypothyroidism causes left ventricle dysfunction, at least in mammals (Fazio et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…(33) Devido à presença de receptores específicos de T3 nas células cardíacas e vasculares (34) , alterações promovidas pela redução da produção dos hormônios tireoidianos implicam em diminuição do débito cardíaco, aumento da resistência vascular periférica, disfunção sistólica e diastólica. Isso ocorre, em grande parte, devido à contratilidade miocárdica comprometida.…”
Section: Potenciais Contribuições Do Exercício Físico Nas Disfunçõesunclassified
“…Some studies reported that apelin increase mRNA expression and activity of SOD, catalase and glutathion peroxidase and decreased MDA (it is the end stage of the lipid peroxidation process and identify for lipid peroxidation evaluation) in cardiac cell and tissue (Aikawa et al 2001;Foussal et al 2010). An absence of thyroid hormones causes morphological and structural changes in cardiac myocytes that brings about changes in hemodynamic characteristics which hypothyroid patient suffering from them (Fazio et al 2004;Klein and Danzi 2007). The oxidant-antioxidant imbalance is one of the reasons in pathogenesis of tissue damage (Halliwell1994).…”
Section: Introductionmentioning
confidence: 99%